PENERAPAN MEDIA METODE TIKRAR DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN DI SMP AL-IMAN ULU-ALE - Ismail, Abdul Wahid; `Anwar, Muh Yunus; Zainal, Abdul Qahar; Wahab, Abdul; Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of Educandy-based interactive learning media in enhancing student learning motivation in the Islamic Religious Education subject for Class X A of the Computer and Network Engineering (TKJ) program at SMK Negeri 1 Topoyo, Central Mamuju Regency. This study aims to examine the implementation of the Tikrar method and the improvement in the quality of Qur’an memorization among Grade VIII A students at SMP Al-Iman Ulu-Ale, Sidenreng Rappang Regency. The study employed Classroom Action Research (CAR) conducted over two cycles, with each cycle comprising the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 29 students. Data collection techniques included observation, interviews, documentation, and memorization tests. The implementation of the Tikrar method involved activities such as reading verses, listening to recitations, repeating verses gradually, memorizing verse by verse, repeating the memorized material until fluent, and reciting the memorized passages to the teacher. Data analysis was conducted both quantitatively and qualitatively by comparing memorization results across the pre-cycle, Cycle I, and Cycle II stages. The results indicate an improvement in the quality of the students' Qur’an memorization following the implementation of the Tikrar method. In the pre-cycle stage, the students' average score was 65.45, with a classical mastery rate of 34.48%. Following the implementation of the Tikrar method in Cycle I, the average score rose to 77.17, with a mastery rate of 68.97%. In Cycle II, the average score increased further to 87.59, with the classical mastery rate reaching 93.10%. These improvements demonstrate that the Tikrar method helps students strengthen their memory, improve recitation fluency, reduce memorization errors, and boost their confidence when reciting memorized passages. Thus, the implementation of the Tikrar method can enhance the quality of Qur’an memorization among Grade VIII A students at SMP Al-Iman Ulu-Ale, Sidenreng Rappang Regency.